1998
DOI: 10.1542/peds.102.5.1135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sleep Position on Infant Motor Development

Abstract: The pattern of early motor development is affected by sleep position. Prone sleepers attain several motor milestones earlier than supine sleepers. However, all infants achieved all milestones within the accepted normal age range. Pediatricians can use this information to reassure parents. This difference in milestone attainment is not a reason to abandon the American Academy of Pediatrics' sleep position recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
158
1
9

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(174 citation statements)
references
References 17 publications
6
158
1
9
Order By: Relevance
“…[6][7][8] For example, several investigators have documented motor delays in otherwise typically developing infants who were positioned frequently in supine position for sleep as recommended by the American Academy of Pediatrics Back to Sleep campaign. 9,10 The Back to Sleep program is believed to have exerted a widespread influence in the U.S. population. 11 Test norms for instruments developed before Back to Sleep may therefore lead to erroneous conclusions about the developmental status of an index group in relation to these norms.…”
mentioning
confidence: 99%
“…[6][7][8] For example, several investigators have documented motor delays in otherwise typically developing infants who were positioned frequently in supine position for sleep as recommended by the American Academy of Pediatrics Back to Sleep campaign. 9,10 The Back to Sleep program is believed to have exerted a widespread influence in the U.S. population. 11 Test norms for instruments developed before Back to Sleep may therefore lead to erroneous conclusions about the developmental status of an index group in relation to these norms.…”
mentioning
confidence: 99%
“…Delayed motor milestones on the Denver Development Screening test were reported for infants of cultures who traditionally place their infants to sleep in the supine position 6) . Similarly, it is reported that infants acquire the motor development faster if they sleep in the prone position 3,4,7) . Dudek-Shriber et al reported that having an understanding of how much time infants spend in the prone position while awake is important for occupational and physical therapists since positioning has been consistenty emphasized as being essential for functional performance 2) .…”
Section: Discussionmentioning
confidence: 80%
“…These results confirm that motor development maturation rates vary even among healthy infants. Infant motor development is influenced by the sleeping position, such as the prone or supine position [2][3][4][5][6][7] . Delayed motor milestones on the Denver Development Screening test were reported for infants of cultures who traditionally place their infants to sleep in the supine position 6) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudo recente observou associações entre as práticas parentais e conhecimento dos pais e o desenvolvimento motor e cognitivo ao longo do tempo 36 , corroborando com os resultados encontrados no estudo. Bebês que dormem em posturas que ofereçam mais oportunidades para o desenvolvimento (de lado ou em prono), tendem a apresentar escores motores superiores [44][45][46] . Estudo prévio sugere que as crianças brasileiras geralmente permanecem muito tempo no colo e raramente são colocadas no chão para brincar nos primeiros seis meses de vida 47 , o que tem sido um indicativo de uma proteção geradora de atraso desenvolvimental 32 .…”
Section: Grupo De Bebês De Mães Adolescentesunclassified